2020
DOI: 10.1002/bab.1875
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 enhances expression of CCL5 to promote recruitment of macrophages and invasion in lung cancer

Abstract: EZH2 (enhancer of zeste homolog 2) regulates epigenetic gene silencing and functions as critical regulators in various tumor progression. Macrophages infiltration promotes cancer development via stimulating tumor cell migration and invasion. However, the effect of EZH2 on macrophages infiltration, cell invasion, and migration of lung cancer remains to be investigated. In this study, we found that knockdown of EZH2 inhibited macrophages chemotaxis and decreased chemokine ligand 5 (CCL5). Wound-healing and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…Among the six hub DEmRNAs, EZH2 has been demonstrated to be highly expressed in HCC, and injection of EZH2 inhibitor GSK126 induces CXCL10 production from macrophages and causes plasma cell polarization, inhibition of the antitumor T cell response, and hepatoma growth (Wei et al, 2019). Additionally, inhibition of EZH2 is also able to affect the macrophage activity in some other cancer types, such as suppressing macrophage infiltration in lung cancer and shifting microglia toward the M1 phenotype in glioblastoma (Yin et al, 2017;Xia et al, 2019). Although the role of DTL, PRC1, KIF4A, ITGA6, and LAMC1 in the regulation of HCC-related macrophages remains unknown, the findings of the mentioned hub DEmRNAs in the regulation of macrophage activity in other diseases may provide the clues for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the six hub DEmRNAs, EZH2 has been demonstrated to be highly expressed in HCC, and injection of EZH2 inhibitor GSK126 induces CXCL10 production from macrophages and causes plasma cell polarization, inhibition of the antitumor T cell response, and hepatoma growth (Wei et al, 2019). Additionally, inhibition of EZH2 is also able to affect the macrophage activity in some other cancer types, such as suppressing macrophage infiltration in lung cancer and shifting microglia toward the M1 phenotype in glioblastoma (Yin et al, 2017;Xia et al, 2019). Although the role of DTL, PRC1, KIF4A, ITGA6, and LAMC1 in the regulation of HCC-related macrophages remains unknown, the findings of the mentioned hub DEmRNAs in the regulation of macrophage activity in other diseases may provide the clues for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Human lung cancer cell lines-A549 and A129L cells were transfected with shRNA, migration ability was determined by wound healing assay and invasion ability was determined by transwell assay, and the results showed that knockdown of EZH2 markedly decreased migration and invasion ability of A549 and A129L cells. Besides, matrix-metalloproteinases (MMPs), which were closely related to the cancer cells invasion and metastasis, were downregulated by EZH2 knockdown [34].…”
Section: Role Of Ezh2 In Cancer Cells Metastasismentioning
confidence: 99%
“…Reduced tumor cell migration and invasion, suppressed metastasis and macrophage infiltration in xenografts [135] Melanoma mCCR5-Ig Increased survival of tumor-bearing mice and decreased migration and immunosuppressive potential of MDSCs [136,137] Ovarian cancer…”
Section: Treatment Effects Referencementioning
confidence: 99%
“…Accordingly, miR-147-overexpressing cancer cells injected subcutaneously into mice inhibited tumor xenograft growth, showing reduced CCL5 expression, invasion, and decreased metastasis formation [134]. CCL5 is modulated at the epigenetic level by EZH2 (enhancer of zeste homolog 2) gene [135]. In vitro, EZH2 knockdown in lung cancer cells decreased CCL5 expression, resulting in reduced chemotaxis of macrophages.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation